Age discrimination in the aspect of organizational practices and age management - Lubrańska, Anna (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The main aim of this article is to present the results of an age discrimination in the organization, in the addition of an age management’s context. Age management is a term that becomes more and more often considered within characteristics of organizational phenomena related to demographic changes in the working population. Therefore the general purpose of this research is the analysis of the relationship between an age management and age discrimination. There were examined 395 working persons (233 women and 162 men). The results of the statistically analysis (cross tabs) showed significant relationships between level of age management, type of the organizational climate and age discrimination.